‘Myth’ or Fact: Textual Analysis on Social Media Postings of Health Issues - Eveline S , Audrey; Sharron B, Kezia (Smart Edu Center, 2023)
The use of social media such as Instagram and TikTok is increasingly widespread. Its use is not just to meet the need to communicate but also to disseminate information. Not all information on social media is not all true. Social media has become a means of spreading false information. By applying textual analysis, this paper aims to examine how Instagram and TikTok postings of health issues communicate health information. The findings show that the contents of the postings are misleading, fabricated content, false, and manipulated. It can be concluded that the postings deliver information based on ‘myth’ rather than the correct medical facts